New technology transforms tactics in Afghanistan [warfare technology]. - Kariya, S.
The astonishingly successful US bombing campaign in Afghanistan marks the beginning of a new era of battle. For the first time in the history of air warfare, a largely remote onslaught toppled a hostile government. This paper examines how the wide use of precision-guided bombs has revolutionized warfare
Keywords: Afghanistan; USA; Air warfare; Bombing campaign; Combat strategy; Precision-guided bombs; Warfare technology